Students’ Conjectures on Open Classical Analogy Problem: Expanding or Narrowing? - Rosyidi, Abdul Haris; Sa’dijah, Cholish; Subanji, Subanji; Sulandra, I Made (FKIP Universitas Lampung, 2024)
Abstract: Students' Conjectures on Open Classical Analogy Problem: Expanding or Narrowing?. Objectives: This study aims to describe students' mathematical conjecture in the context of open classical analogy problem. Methods: This descriptive research describes students' conjectural profiles using open classical analogies. Data were collected from the responses of 68 students. Data analyzed using constructor example, process, and quality of the conjecture. Findings: Results show that the example of constructing the conjecture has not paid attention to all possible cases, while the process of the conjecture used by students was from simple to more expanding or narrowing. Some of the proposed conjecture quality does not include the necessary constraints, and some include unnecessary limitations. Students can add to statements that sharpen the conjecture proposed previously. Conclusion: The results of this study indicate that in the construction of conjectures in the context of an open classical analogy, students involve their critical thinking skills. Keywords: conjecture, example, open classical analogy, process, quality of conjecture.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202419